Tuning in to the male: evidence contradicting sexually antagonistic coevolution models of sexual selection in Leucauge mariana (Araneae Tetragnathidae). Issue 2 (3rd March 2020) - Segura-Hernández, Laura; Aisenberg, Anita; Vargas, Eric; Hernández-Durán, Linda; Eberhard, William G.; Barrantes, Gilbert
Abstract : Male courtship signals often stimulate female sense organs whose sensitivities originally evolved under natural selection. In classic female choice models of sexual selection, females can benefit from increasing their sensitivity and responsiveness to male stimuli; but in sexually antagonistic models, increased female sensitivity or responsiveness to males could increase the costs that females are thought to suffer from male stimulation. We tested these contrasting expectations in a previously discovered sexually dimorphic trait in the spider Leucauge mariana : 12 elongate setae on the female's sternum that are deflected by movements of the male's cheliceral fangs during copulation. By removing these setae, we tested whether this stimulation induces female responses that favor the male's chances of paternity. We found that these stimuli induced females to add a product crucial to the formation of copulatory plugs. These results do not fit expectations from sexually antagonistic coevolution models of sexual selection. This conclusion resembles the heretofore unappreciated implications of specialized female sense organs in other species, and of the temporary increases in female sensitivities and responsiveness to male stimuli during the breeding season in female fish and frogs.